Information Infrastructures: the Conduit Power of ICTs in Africa (The Strategic Review for Southern Africa, 2020)
In this article, I make a case for considering Information and Communications Technology (ICT) infrastructures outside the narrow prism of ICT for development (ICT4D), but rather as an alternate mechanism to exercise political power in Africa. I refer to ‘infrastructures’ rather than ‘infrastructure’ because the former has a broader definition. Infrastructures may be material, informational or structural. Infrastructure relates to the physical and organisational structure and facilities a society or an organisation needs to function, such as roads, electricity and communication systems. Owing to the inability to overcome weaknesses in state capacity, the expression of power in the global South often differs from the global North. ICT infrastructure is transnational with power oscillating between state and non-state actors but offers African countries a surrogate system of administration for individual territories. I draw on the concept of infrastructural power to describe how a state may harness ICT infrastructure, or information infrastructures, to increase its influence within its territory and extraterritorially.